Preparation method of carbon-doped carbon nitride material as well as product and application of carbon-doped carbon nitride material
The preparation of carbon doped carbon nitride materials through prepolymerization and supramolecular modification has solved the serious problem of photogenerated carrier recombination of existing carbon nitride materials and achieved a more efficient photocatalytic effect.
Patent Information
- Application Number
- CN202411422876.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
AI Technical Summary
The existing carbon nitride materials have severe photogenerated carrier recombination in photocatalysis, resulting in low visible light utilization and poor catalytic effect.
The carbon-doped meleamine precursor is formed through prepolymerization, and the heptaazine supramolecular structure connected by hydrogen halogen bond is introduced by supramolecular modification method, and carbon-doped carbon nitride material is calcined at high temperature to destroy the plane-symmetric structure. Broaden the optical response range and improve photogenerated carrier migration and separation.
The specific surface area and pore structure of the material are improved, the absorption of sunlight and the adsorption and activation of reactants are enhanced, and the photocatalytic efficiency is significantly improved.
Smart Images

Figure CN119500211A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysts, and in particular relates to a preparation method of a carbon-doped carbon nitride material, a product thereof and an application thereof. Background Art
[0002] Compared with the traditional method of preparing aromatic aldehydes and aromatic carboxylic acids by side chain chlorination and oxidation of toluene as raw material, the benzyl alcohol oxidation method has the advantages of simple process and relatively green environmental protection, but it still needs to adopt high temperature and high pressure under the action of precious metal and non-precious metal-based catalysts, and is often accompanied by the generation of by-products, which affects the yield. Photocatalytic technology uses green sunlight as energy and semiconductor materials as catalysts to achieve selective oxidation of benzyl alcohol under mild conditions. The development of semiconductor materials with suitable band gap width and oxidation / reduction ability, as well as excellent stability has always been a research hotspot in this field. Compared with traditional metal-based semiconductor catalytic materials, graphite phase carbon nitride (g-C3N4) has the characteristics of simple preparation, abundant raw materials, adjustable physical and chemical properties, acid and alkali resistance, etc., and has attracted widespread attention. However, bulk carbon nitride obtained by direct thermal polymerization using nitrogen-containing small molecules (such as melamine, urea, dicyandiamide, etc.) as precursors usually has a small specific surface area, serious photogenerated carrier recombination, low visible light utilization, and often fails to achieve the expected effect in catalysis. Therefore, in order to improve the activity of carbon nitride materials, they need to be modified. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a carbon-doped carbon nitride material and its products and applications in view of the above shortcomings.
[0004] On the one hand, the present invention provides a method for preparing a carbon-doped carbon nitride material, the specific steps of which are:
[0005] (1) Prepolymerization: a certain proportion of melamine and 2,4,6-triaminopyrimidine powder are mixed, heated to 400-450°C in a protective gas atmosphere, and calcined to form a prepolymer carbon-doped melem;
[0006] (2) Supramolecular modification: 0.5 g of carbon-doped melem obtained in step (1) was added to 25 mL of a hydrochloric acid aqueous solution of a certain concentration, dispersed by ultrasonic oscillation, and then placed in a fume hood to naturally evaporate the water and excess hydrochloric acid, and further dried and ground to obtain a carbon-doped heptazine supramolecular precursor connected by hydrogen-halogen bonds;
[0007] (3) Preparation of carbon nitride by high temperature calcination: The carbon-doped heptazine supramolecular precursor connected by hydrogen-halogen bonds obtained in step (2) is calcined at 500-600° C. for 2-6 h, and then crushed and ground after cooling to obtain a carbon-doped carbon nitride photocatalytic material.
[0008] By the method provided by the present invention, a prepolymer is first prepared, which has high thermal stability and a heptazine skeleton structure similar to that of g-C3N4, and then supramolecular modification is performed by hydrochloric acid, and finally high-temperature calcination is performed, so that not only a rich pore structure can be obtained, and the material's absorption of sunlight and adsorption capacity of reactant molecules can be improved, but also modification units (such as vacancies, tris-s-triazine-like units, modified functional groups, etc.) can be implanted into the carbon nitride skeleton to destroy the planar symmetrical tris-s-triazine structure, stimulate n→π* electronic transition, broaden the visible light absorption range of the material, and adjust the charge distribution of the material to further promote the adsorption and activation of the reactant molecules; and the band structure is adjusted to improve the separation and migration behavior of photogenerated carriers, so as to obtain better oxidation / reduction ability.
[0009] Furthermore, the calcination time in step (1) is 4 to 16 hours.
[0010] Furthermore, in step (1), the heating rate is 5°C·min -1 The calcination temperature is 425℃ and the calcination time is 6h.
[0011] Furthermore, in the step (1), the mass ratio of melamine to 2,4,6-triaminopyrimidine is 10:0.05-1.0.
[0012] Furthermore, in step (1), the protective gas is N2 or Ar.
[0013] Furthermore, in step (2), the preparation method of 25 mL of hydrochloric acid aqueous solution is to take y mL of concentrated hydrochloric acid and add it to (25-y) mL of pure water, where the value of y is 0.5 to 4.
[0014] The second aspect of the present invention also provides a carbon-doped carbon nitride material prepared by the above preparation method.
[0015] The third aspect of the present invention also provides an application of the above carbon-doped carbon nitride material in photocatalytic selective oxidation.
[0016] Furthermore, the application is to use benzyl alcohol as a reaction substrate, acetonitrile as a reaction medium, carbon-doped carbon nitride as a photocatalyst, a xenon lamp as a light source, add an oxidant, form a reaction system, and prepare benzaldehyde and / or benzoic acid.
[0017] Furthermore, the reaction conditions are as follows: the reaction temperature is controlled at 60°C, the reaction time is 1 to 8 hours, and the concentration of benzyl alcohol in the reaction system is 50 mmol·L -1 , the carbon nitride photocatalyst concentration is 4 g·L -1 , the oxidant is oxygen.
[0018] Beneficial effects of the present invention:
[0019] (1) First, melamine and 2,4,6-triaminopyrimidine are prepolymerized at a relatively low temperature (400-450°C) to form a prepolymer. The prepolymer generates a carbon-doped melem precursor, which has high thermal stability and can effectively slow down the rapid sublimation of the precursor during the subsequent calcination process, so that the prepared carbonized carbon has good structural integrity and promotes the migration of photogenerated carriers. The prepolymer improves the stability of the precursor and improves the orderliness and integrity of the microstructure of the final carbon nitride material.
[0020] (2) The carbon nitride prepared by calcining the heptazine supramolecular molecule connected by hydrogen-halogen bonds has a rich pore structure and specific surface area, which is conducive to light absorption and reactant adsorption. The hydrogen-halogen bond effect and the heptazine ring structure precursor provide more possibilities for the design of supramolecular precursors for the preparation of carbon nitride.
[0021] (3) TAP doping can introduce pyrimidine rings into the carbon nitride skeleton, breaking the symmetric structure of the carbon nitride heptazine skeleton, stimulating n→π* transitions, and broadening the photoresponse range of the material; at the same time, carbon doping is also beneficial to the migration and separation of photogenerated carriers, thereby improving the photocatalytic efficiency.
[0022] (4) The carbon-doped carbon nitride material prepared by the method of the present invention is used in the photocatalytic selective oxidation of benzyl alcohol. The selective oxidation of benzyl alcohol is carried out in a multiphase catalytic system, and the catalyst is easy to separate and recover. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 CN-MTAP prepared in Example 3 0.5 SEM image of Cl1;
[0024] Figure 2 CN-MTAP prepared in Example 3 0.5 TEM image of Cl1;
[0025] Figure 3 XRD patterns of carbon-doped carbon nitride prepared in Examples 1 to 4;
[0026] Figure 4 XRD patterns of carbon-doped carbon nitride prepared in Examples 5 to 8;
[0027] Figure 5 The carbon nitride CN-MTAP prepared in Example 3 and Comparative Examples 1 to 3 0.5 Cl1, CN-melem, CN-MelCl1 and CN-MTAP 0.5 XRD pattern of Cl1;
[0028] Figure 6 The carbon nitrides CN-M, CN-melem, CN-MelCl1 and CN-MTAP prepared in Example 3 and Comparative Examples 1 to 3 0.5N2 adsorption-desorption curve of Cl1;
[0029] Figure 7 The carbon nitrides CN-M, CN-melem, CN-MelCl1 and CN-MTAP prepared in Example 3 and Comparative Examples 1 to 3 0.5 UV-visible diffuse reflectance spectrum of Cl1;
[0030] Figure 8 The carbon nitrides CN-M, CN-melem, CN-MelCl1 and CN-MTAP prepared in Example 3 and Comparative Examples 1 to 3 0.5 The corresponding Tauc plot of Cl1. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification. The methods described are all conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.
[0032] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0033] The method for preparing the carbon-doped carbon nitride material provided by the present invention comprises the following specific steps:
[0034] (1) Prepolymerization: a certain proportion of melamine and 2,4,6-triaminopyrimidine powder are mixed, heated to 400-450°C in a protective gas atmosphere, and calcined to form a prepolymer carbon-doped melem;
[0035] (2) Supramolecular modification: 0.5 g of carbon-doped melem obtained in step (1) was added to 25 mL of a hydrochloric acid aqueous solution of a certain concentration, dispersed by ultrasonic oscillation, and then placed in a fume hood to naturally evaporate the water and excess hydrochloric acid, and further dried and ground to obtain a carbon-doped heptazine supramolecular precursor connected by hydrogen-halogen bonds;
[0036] (3) Preparation of carbon nitride by high temperature calcination: The carbon-doped heptazine supramolecular precursor connected by hydrogen-halogen bonds obtained in step (2) is calcined at 500-600° C. for 2-6 h, and then crushed and ground after cooling to obtain a carbon-doped carbon nitride photocatalytic material.
[0037] The following is a detailed description of the raw material feeding amount and the specific reaction conditions in the examples.
[0038] Carbon-doped carbon nitride materials are labeled as (CN-MTAPx Cl y , wherein x is the amount of TAP (g) when M is 10g; y is the amount of concentrated hydrochloric acid (mL) required to prepare a total volume of 25mL of hydrochloric acid solution. The concentration of concentrated hydrochloric acid in the present invention is 38%. M refers to melamine, and TAP refers to 2,4,6-triaminopyrimidine.
[0039] Example 1
[0040] CN-MTAP 0.05 Preparation of Cl1 catalyst:
[0041] (1) 10 g of melamine and 0.05 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0042] (2) Take 0.5 g of carbon-doped melem in step (1), add 1 mL of concentrated hydrochloric acid and 24 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0043] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride photocatalytic material CN-MTAP. 0.05 Cl1.
[0044] Example 2
[0045] CN-MTAP 0.1 Preparation of Cl1:
[0046] (1) 10 g of melamine and 0.1 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0047] (2) Take 0.5 g of carbon-doped melem in step (1), add 1 mL of concentrated hydrochloric acid and 24 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0048] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride photocatalytic material CN-MTAP. 0.1 Cl1.
[0049] Example 3
[0050] CN-MTAP 05 Preparation of Cl1:
[0051] (1) 10 g of melamine and 0.5 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0052] (2) Take 0.5 g of carbon-doped melem in step (1), add 1 mL of concentrated hydrochloric acid and 24 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0053] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride material CN-MTAP. 0.5 Cl1. CN-MTAP 0.5 Cl1 samples were sent for testing.
[0054] from Figure 1 and Figure 2 Analysis shows that the prepared CN-MTAP 0.5 Cl1 has a porous structure, which is conducive to the increase of specific surface area and the adsorption and activation of reactants.
[0055] Example 4
[0056] CN-MTAP 1.0 Preparation of Cl1:
[0057] (1) 10 g of melamine and 1.0 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0058] (2) Take 0.5 g of carbon-doped melem in step (1), add 1 mL of concentrated hydrochloric acid and 24 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0059] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride material CN-MTAP. 1.0 Cl1.
[0060] The carbon-doped carbon nitride materials prepared in Examples 1-4 were sent for testing. Figure 3 The XRD patterns of carbon-doped carbon nitride materials prepared by adding different mass TAP precursors. All samples have diffraction peaks at 2θ=13 and 27°, corresponding to the (100) and (002) crystal planes of carbon nitride materials. The ratio of the diffraction peaks of the crystal planes I (002) / I (100) It will change with the addition of TAP, but it will not change the main framework structure of the final carbon nitride material.
[0061] CN-MTAP 0.5 Cl 0.5 Preparation:
[0062] (1) 10 g of melamine and 0.5 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0063] (2) Take 0.5 g of carbon-doped melem in step (1), add 0.5 mL of concentrated hydrochloric acid and 24.5 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0064] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride material CN-MTAP. 0.5 Cl 0.5 .
[0065] Example 6
[0066] CN-MTAP 0.5 Preparation of Cl2:
[0067] (1) 10 g of melamine and 0.5 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0068] (2) Take 0.5 g of carbon-doped melem in step (1), add 2 mL of concentrated hydrochloric acid and 23 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0069] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride material CN-MTAP. 0.5 Cl2.
[0070] Example 7
[0071] CN-MTAP 0.5 Preparation of Cl4:
[0072] (1) 10 g of melamine and 0.5 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0073] (2) Take 0.5 g of the carbon-doped melem in step (1), add 4 mL of concentrated hydrochloric acid and 21 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0074] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride material CN-MTAP. 0.5 Cl4.
[0075] Example 8
[0076] CN-MTAP 0.5 Cl 10 Preparation:
[0077] (1) 10 g of melamine and 0.5 g of 2,4,6-triaminopyrimidine powder were mixed, and the mixture was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0078] (2) Take 0.5 g of carbon-doped melem in step (1), add 10 mL of concentrated hydrochloric acid and 15 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a hydrogen-chloride bonded carbon-doped heptazine supramolecular precursor.
[0079] (3) 0.5 g of the hydrogen-chlorine bonded carbon-doped heptazine supramolecular precursor in step (2) was calcined at 550 °C for 4 h in air, with a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride material CN-MTAP. 0.5 Cl 10 .
[0080] It should be noted that the amounts of M and TAP, ie, the x value, and the amount of concentrated hydrochloric acid, ie, the y value, include but are not limited to the ratios listed in the examples.
[0081] Figure 4 The XRD diagram of the carbon-doped carbon nitride material prepared by adding Examples 5 to 8. Similarly, all samples have diffraction peaks at 2θ=13 and 27°, corresponding to the (100) and (002) crystal planes of the carbon nitride material. As the amount of hydrochloric acid added increases, no new diffraction peaks appear, and the positions of the (100) and (002) crystal plane diffraction peaks remain unchanged, indicating that the heptazine supramolecules formed by calcining hydrochloric acid of different concentrations will eventually generate heptazine-based nitrogen nitride; however, the crystal plane diffraction peak intensity is higher than that of I (002) / I (100) This indicates that the carbon nitride material prepared with the heptazine supramolecule obtained under higher concentration of hydrochloric acid as precursor has fewer stacking layers and lower crystallinity.
[0082] Comparative Example 1
[0083] Preparation of bulk carbon nitride (CN-M):
[0084] Take 0.5 g of melamine powder and calcine it at 550 °C for 4 h in air, with a heating rate of 5 °C min -1After calcination, the solid is naturally cooled and ground to obtain bulk carbon nitride material CN-M.
[0085] Comparative Example 2
[0086] Preparation of CN-melem:
[0087] (1) 10 g of melamine powder was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0088] (2) Take 0.5 g of the melem precursor in step (1) and calcine it at 550 °C for 4 h in air at a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon-doped carbon nitride material CN-melem.
[0089] Comparative Example 3
[0090] Preparation of CN-MelCl1:
[0091] (1) 10 g of melamine powder was heated to 425° C. in a N 2 atmosphere and calcined for 6 h to form carbon-doped melem, which was then fully ground and set aside.
[0092] (2) Take 0.5 g of melem in step (1), add 1 mL of concentrated hydrochloric acid and 24 mL of H2O, and after ultrasonic dispersion for 10 min, oscillate in an oscillator for 24 h. Subsequently, the reactants are placed in a fume hood to naturally evaporate water and excess hydrochloric acid, and further dried at 40° C. and ground to obtain a heptazine supramolecular precursor connected by hydrogen-chlorine bonds.
[0093] (3) 0.5 g of the heptazine supramolecular precursor connected by hydrogen-chlorine bonds in step (2) was calcined at 550 °C for 4 h in air at a heating rate of 5 °C min -1 After calcination, the solid was naturally cooled and ground to obtain the carbon nitride material CN-MelCl1.
[0094] Figure 5The XRD patterns of carbon nitride materials prepared in Example 3 and Comparative Examples 1 to 3. Similarly, all samples have diffraction peaks at 2θ=13 and 27°, corresponding to the (100) and (002) crystal planes of carbon nitride materials. No new diffraction peaks appear in the XRD pattern of the material after TAP incorporation and supramolecular modification, and the positions of the (100) and (002) crystal plane diffraction peaks remain unchanged, indicating that heptazine-based nitrogen nitride will be generated after calcination when melamine, melem, melem supramolecular, and carbon-doped melem supramolecular are used as precursors. However, supramolecular modification will greatly reduce the intensity of the (100) diffraction peak, indicating that supramolecular modification is conducive to obtaining carbon nitride materials with fewer layers, which plays a positive role in improving the specific surface area of the material.
[0095] Figure 6 The N2 adsorption-desorption curves of the carbon nitride materials prepared in Example 3 and Comparative Examples 1 to 3 are shown in the figure. As can be seen from the figure, the supramolecular modification and the introduction of TAP in the precursor can greatly increase the specific surface area of the material. Compared with the bulk carbon nitride (CN-M, 8.1 m 2 g -1 ), in Example 3, carbon nitride CN-MTAP 0.5 The specific surface area of Cl1 is as high as 42.8m 2 g -1 .
[0096] Figure 7 The UV-visible absorption diffuse reflectance spectra of the carbon nitride materials prepared in Example 3 and Comparative Examples 1 to 3. With the supramolecular modification and further carbon doping, the absorption sideband of carbon nitride gradually red-shifts and the light absorption range is broadened.
[0097] Figure 8 Tauc plots of the carbon nitride materials prepared in Example 3 and Comparative Examples 1-3.
[0098] CN-M, CN-melem, CN-MelCl1 and CN-MTAP 0.5 The bandgap widths of Cl1 are
[0099] 2.79, 2.72, 2.66 and 2.48 eV. Among them, CN-MTAP 0.5 Cl1 is most conducive to light absorption.
[0100] The carbon nitride materials prepared in the above-mentioned embodiments and control examples were respectively applied to the selective oxidation reaction of benzyl alcohol as a photocatalyst. The specific experimental steps are as follows:
[0101] 8 mg of each carbon nitride material prepared in the above embodiments and control examples was placed in a quartz reaction tube, 4 mL of acetonitrile was added, 0.1 mmol of benzyl alcohol was added after ultrasonic dispersion, the air in the tube was replaced with O2, the tube was sealed, and an oxygen balloon was connected to react. The light source was a Xe lamp, and the reaction temperature was controlled at 60°C; the product was detected by liquid chromatography, and the conversion rate and selectivity were calculated by the external standard method.
[0102] Table 1 CN-MTAP 0.5 Effect of reaction conditions on catalytic results with Cl1 catalyst
[0103]
[0104] "+" means adding the item; "-" means not adding the item
[0105] Table 1 shows the usage of CN-MTAP 0.5 Cl 1为 The effect of reaction conditions on the reaction results under the presence of catalysts. The data show that the oxidation reaction of benzyl alcohol cannot proceed without catalysts or light (No. 1, 2). Therefore, it can be concluded that light and catalysts are indispensable for this reaction. When the reaction system is filled with Ar (No. 3), the reaction conversion rate is lower than that with O2 as the reaction atmosphere (No. 4, 5). However, as the reaction atmosphere, the only product is benzaldehyde, indicating that the photogenerated holes generated by the carbon nitride catalyst under light conditions can only oxidize benzyl alcohol to benzaldehyde, and cannot be further oxidized to generate benzoic acid; while under the presence of O2, the superoxide radicals generated by light can further oxidize benzaldehyde to benzoic acid. Therefore, the product selectivity can be controlled by controlling the reaction atmosphere. Benzoquinone, triethanolamine and K2S2O8 were added to the reaction system as superoxide radicals, photogenerated holes and electron capture agents, respectively. Compared with benzoquinone and triethanolamine, the conversion rate of benzyl alcohol was significantly reduced after triethanolamine was added to the reaction system (No. 6, 7), indicating that compared with superoxide radicals, photogenerated holes are the key factor affecting the reaction. Adding K2S2O8 to capture photogenerated electrons and inhibit the recombination of photogenerated holes and electrons can greatly improve the reaction efficiency. By controlling the reaction atmosphere, complete conversion of benzaldehyde or benzoic acid can be achieved (No. 8, 9).
[0106] Table 2 Comparison of performance of various catalysts
[0107]
[0108] Table 2 shows the comparison of the catalyst activities in the prepared examples and the control examples under the conditions of light and O2, with the reaction time controlled to 4h. 0.5Cl1 has the best catalytic activity, and the product is mainly benzoic acid. During the catalyst optimization process, the catalyst activity tends to rise first and then fall with the increase of TAP doping amount, mainly because excessive carbon doping will affect the carbon nitride skeleton structure, which is not conducive to light absorption and photogenerated carrier separation; changing the amount of hydrochloric acid, the material activity also rises first and then falls. Since the supramolecular structure formed by the heptazine precursor and HCl will not change significantly due to the increase in the amount of hydrochloric acid added, the catalyst activity decreases less after the addition of excess hydrochloric acid. Compared with the carbon nitride catalysts in Control Examples 1 to 3, carbon doping and supramolecular modification can significantly improve the catalytic activity of the material.
Claims
1. A method for preparing a carbon-doped carbon nitride material, characterized in that: The specific steps are: (1) Prepolymerization: a certain proportion of melamine and 2,4,6-triaminopyrimidine powder are mixed, heated to 400-450°C in a protective gas atmosphere, and calcined to form a prepolymer carbon-doped melem; (2) Supramolecular modification: 0.5 g of carbon-doped melem obtained in step (1) was added to 25 mL of a hydrochloric acid aqueous solution of a certain concentration, dispersed by ultrasonic oscillation, and then placed in a fume hood to naturally evaporate the water and excess hydrochloric acid, and further dried and ground to obtain a carbon-doped heptazine supramolecular precursor connected by hydrogen-halogen bonds; (3) Preparation of carbon nitride by high temperature calcination: The carbon-doped heptazine supramolecular precursor connected by hydrogen-halogen bonds obtained in step (2) is calcined at 500-600° C. for 2-6 h, and then crushed and ground after cooling to obtain a carbon-doped carbon nitride photocatalytic material.
2. A method for preparing the carbon-doped carbon nitride material according to claim 1, characterized in that: The calcination time in step (1) is 4 to 16 hours.
3. The method for preparing the carbon-doped carbon nitride material according to claim 1, characterized in that: In the step (1), the heating rate is 5°C min -1 The calcination temperature is 425℃ and the calcination time is 6h.
4. The method for preparing the carbon-doped carbon nitride material according to claim 2, characterized in that: In the step (1), the mass ratio of melamine to 2,4,6-triaminopyrimidine is 10:0.05-1.
0.
5. The method for preparing the carbon-doped carbon nitride material according to claim 1, characterized in that: In the step (1), the protective gas is N2 or Ar.
6. The method for preparing the carbon-doped carbon nitride material according to claim 2, characterized in that: In the step (2), the preparation method of 25 mL of hydrochloric acid aqueous solution is to take y mL of concentrated hydrochloric acid and add it to (25-y) mL of pure water, where the value of X is 0.5-4.
7. A carbon-doped carbon nitride material, characterized in that: The invention is prepared by the method according to any one of claims 1 to 6.
8. Use of the carbon-doped carbon nitride material as claimed in claim 7 in photocatalytic selective oxidation.
9. The use of the carbon-doped carbon nitride material in photocatalytic selective oxidation as claimed in claim 8, characterized in that: Benzyl alcohol is used as a reaction substrate, acetonitrile is used as a reaction medium, carbon-doped carbon nitride is used as a photocatalyst, a xenon lamp is used as a light source, an oxidant is added, a reaction system is formed, and benzaldehyde and / or benzoic acid are prepared.
10. The use of the carbon-doped carbon nitride material in photocatalytic selective oxidation as claimed in claim 9, characterized in that: The reaction conditions are: the reaction temperature is controlled at 60°C, the reaction time is 1 to 8 hours, and the concentration of benzyl alcohol in the reaction system is 50 mmol·L -1 , the carbon nitride photocatalyst concentration is 4 g·L -1 , the oxidant is oxygen.
Citation Information
Patent Citations
Sulfur-doped crystal carbon nitride for photocatalytic decomposition of water to produce hydrogen and preparation method and application thereof
CN112473713A
Preparation method and application of spherical crystalline carbon nitride with heptazine ring structure
CN114920219A
Preparation method and application of carbon nitride semiconductor photocatalyst containing heptazine / triazine homojunction structure
CN117101701A
Method for producing a photocatalyst for water decomposition reaction based on molecular doped carbon nitride
RU2791361C1
Phosphorus-doped tubular carbon nitride micro-nano material and application thereof in catalytic treatment of exhaust gas
US20200282384A1
Cited By
Carbon-doped carbon nitride nanotube, preparation method thereof and application of carbon-doped carbon nitride nanotube in photocatalytic reaction
CN120885254A